1977
DOI: 10.1139/v77-127
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylamino acids in peptide synthesis. VII. Studies on the enantiomeric purity of N-methylamino acids prepared by various procedures

Abstract: The enantiomeric purity of N-methylamino acids and their derivatives obtained by various procedures has been examined by analysis with an amino-acid analyzer of the diastereomeric lysyl dipeptides formed by coupling them with a lysyl derivative. N-Benzyloxycarbonyl, and N-tert-butyloxycarbonyl,N-methylamino acids obtained by methylation of the parent derivative using sodium hydride and methyl iodide, and N-methylamino acids obtained by methylation of the p-toluenesulfonylamino acid followed by treatment with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…It is known that N α -protected- N α -methylamino acid methyl esters racemize more readily during saponification than the corresponding amino acid esters. 15c, Racemization was also observed in our case during saponification of 3b and 3h using 2 M LiOH in THF or methanol. Racemization could be observed by 1 H NMR with the appearance of a new doublet next to the normal αH doublet.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…It is known that N α -protected- N α -methylamino acid methyl esters racemize more readily during saponification than the corresponding amino acid esters. 15c, Racemization was also observed in our case during saponification of 3b and 3h using 2 M LiOH in THF or methanol. Racemization could be observed by 1 H NMR with the appearance of a new doublet next to the normal αH doublet.…”
Section: Resultssupporting
confidence: 70%
“…Methods involving reductive amination, Mitsunobu reaction, Diels−Alder/retro-Diels−Alder sequences, and alternative procedures have also been developed . Unfortunately, most of these methods are limited to aliphatic amino acids or are characterized by harsh reaction conditions or long synthetic sequences, and some cause partial racemization of the substrate. 13f,15b, In general, the methods above show limited or no application to N α -methylamino acids with functionalized side-chains and are incompatible with Fmoc solid-phase peptide synthesis (Fmoc-SPPS) side-chain protecting groups (Boc, Trt, t -Bu). Therefore, we were interested in developing a fast, easy, and highly efficient procedure to prepare side-chain protected N α -methylamino acids in large quantities with the possibility of using them directly in Fmoc-SPPS.…”
Section: Introductionmentioning
confidence: 99%
“…Chemistry. Several methods for N -methylation of amino acids are known in the literature. Following the Fmoc strategy in peptide synthesis, the method of Freidinger et al is most favorable as it results in N -methylated Fmoc-protected amino acids in good overall yields without racemization. N -Methylation is achieved by condensation of the Fmoc-protected amino acid with paraformaldehyde, resulting in an oxazolidinone which can be opened under acidic, reductive conditions to give the desired N -methyl amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…However, potential exists when using a strong base for racemization of the chiral center. [3] In previous studies, we have shown that 1,3-oxazolidin-5-ones 1 are useful substrates for the synthesis of N-methyl-a-amino acids 2 and Nmethyl-b-amino acids 3 (Scheme 1). [4][5][6][7][8][9] In addition, we have also shown that the homologous 1,3-oxazinan-6-ones 4 are versatile precursors for gaining access to a range of N-methyl-b-amino acids 3 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%